Roasting, grinding, and storage impact onthermodynamic properties and adsorptionisotherms of arabica coffee - de Oliveira, Gabriel Henrique Horta (2017)
This work aimed to evaluate alterations on the water sorption of coffee due toroast, grind, and storage. Crude grain coffee (Coffea arabica) was roasted at twolevels: medium light and moderately dark. Grain was grinded in ﬁne (0.59 mm ),medium (0.84 mm), and coarse (1.19 mm) particle sizes, besides the whole coffeelot. Samples were then stored at polypropylene bags and kept at biochem ical oxy-gen demand type chambers in two storage temperatures (10 and 30C). Thesewere analyzed at 0, 30, 60, 120, and 180 days, regarding water content and wate ractivity. Mathematical modeling and thermodynamic properties of coffee mois-ture adsorption process were accomplished. It was concluded that particle size didnot signiﬁcantly affect water content of coffee, independently of roast degree.Sigma-Copace model best represented hygroscopic equilibrium of roasted coffee.Water content reduction increases the differential enthalpy and entropy of sorp-tion and Gibbs free energy.